(untitled) (Oratio Directa, 2024)
Social media play an important role in political campaigns because candidates can use them to interact with sympathizers and supporters. Anies Rasyid Baswedan uses Instagram to convey political messages and build engagement. This study examines his political campaign on Instagram through content analysis, focusing on his personality and the political key messages displayed on the platform. The study uses a qualitative approach and analyzes 145 uploads posted by @aniesbaswedan in January 2024. The content-analysis instrument covers campaign strategies, public interaction, and visual symbols and messages. The findings show that Anies Baswedan consistently conveyed campaign messages through social media and that the Desak Anies campaign contributed to the practice of modern democratic engagement.